France : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2003)
This Selected Issues paper first explains the recent increase in trend growth and then discusses how labor market and tax policies could best sustain it. This study calculates French trend growth estimating simultaneously a Cobb-Douglas production technology and total factor productivity. The main conclusion is that French trend growth indeed increased during the second half of the 1990s to an average annual rate of 2.1 percent, from 1.8 percent in 1993. This was not owing to a recovery of total factor productivity growth.